Antidiarrhoeal activity of decoction of Scoparia dulcis in rats - Ratnasooriya, W.D.; Galhena, G.; Liyanage, S.S.P.; Jayakody, J.R.A.C.; Hettiarachchi, A.D.I.; Ediriweera, E.R.S.S. (My University, 2005)
The aim of this study was to investigate the antidiarrhoeal potential of a decoction (D) made from Scoparia dulcis Linn (Family: Scrophulariaceae), as indicated by traditional practitioners in Sri Lanka, using the caster oil-induced diarrhoeal rat model. Different doses of D (500,1500,3000 mg/kg) were orally administrated and antidiarrhoeal activity monitored over a 6 h period. The D induced a significant (P<0.05) and dose- dependent antidiarrhoeal effect from Ih post treatment. This antidiarrhoeal action was mediated via an inhibition in intestinal transit due to impairment of intestinal peristalsis, rather than to an increment in intestinal fluid absorption and/or reduction in secretion. The decoction may have a potential in symptomatic reliefofnon-specific acute diarrhoeas.